(untitled) (Journal of the College of Basic Education, 2022)
The novel (The Beautiful Country) is the novel that won the first prize for the Arabic novel in Dubai in 2005 by the novelist, poet and screenwriter Ahmed Saadawi. More than half a century witnessed an expansion in all fields until the literature that deals with relationships and their types dominated other researches, due to the comprehensiveness of this science, through which it became possible to address any field from a semiotic angle, so fields and researches appeared in language, rhetoric and aesthetics that depend on this science ( semiotics).